2010
DOI: 10.1007/s11552-009-9255-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of the HLA System in the Pathogenesis of Dupuytren's Disease

Abstract: Dupuytren's disease (DD) is a familial, fibroproliferative, irreversible, and progressive disease of the palmar fascia, yet with unknown etiology. However, there is compelling evidence which has consistently suggested a genetic ethiopathogenesis given the high occurrence among the Northern European extraction, familial nature, and demonstration of concordance in twins. DD is an incurable, recurrent, and potentially debilitating disease with limited and ineffective treatments. Although a number of possible cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 63 publications
(176 reference statements)
0
4
0
1
Order By: Relevance
“…It has been suggested that DD is a T cell–mediated autoimmune disorder, largely based on the discovery of dense T-cell infiltrates in DD nodules 24 . Other studies have confirmed the presence of different T-cell populations in nodules, including T helper cells 27 . A recent study showed the presence of an activated T-cell infiltrate adjacent to blood vessels within the nodules and these cells expressed a restricted T-cell receptor repertoire in vitro .…”
Section: Emerging Concepts In the Pathogenesis Of Dupuytren’s Diseasementioning
confidence: 80%
“…It has been suggested that DD is a T cell–mediated autoimmune disorder, largely based on the discovery of dense T-cell infiltrates in DD nodules 24 . Other studies have confirmed the presence of different T-cell populations in nodules, including T helper cells 27 . A recent study showed the presence of an activated T-cell infiltrate adjacent to blood vessels within the nodules and these cells expressed a restricted T-cell receptor repertoire in vitro .…”
Section: Emerging Concepts In the Pathogenesis Of Dupuytren’s Diseasementioning
confidence: 80%
“…Группы сопоставимы по клинико-демографическим характеристикам, но достоверно отличаются по частоте ранних рецидивов контрактуры Дюпюитрена, что свидетельствует о патогенетически значимой роли грибковой инвазии как повреждающего фактора, инициирующего активность фасциального фиброматоза. Характерные для болезни Дюпюитрена иммуногенетические особенности [28] формируют общие (системные) факторы риска грибковой инвазии. Вовлечение в фиброматозный процесс кожи [29] нарушает её барьерные свойства и создаёт местные условия для внедрения возбудителей инфекции в глубже лежащие ткани.…”
Section: клинические исследованияunclassified
“…A maternally transmitted inheritance pattern has been shown among Caucasian DD patients; 90% showed a mutation within the mitochondrial 16s rRNA gene [8]. Specific human leukocyte alleles, in particular the class II HLA-DR loci, are associated with a predilection for or protection against DD [9]. A study in 960 patients with Dupuytren's identified nine different loci involved in genetic susceptibility to the disease; six of these loci harbored genes encoding the Wnt signaling pathway [10], part of…”
Section: Pathogenesismentioning
confidence: 99%